PENINGKATAN KETERAMPILAN MENGADAKAN VARIASI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN KIMIA - Tuti Kurniati; Ucu Liani (Jurnal Ilmiah Ar-Razi, 2019)
The purpose of this research was to improve variation skills of student at chemical education. Meanwhile, the method of this research was classroom action research which conducted in the two cycles. The research design was begun by planning, action, observation, reflection and continued by the next planning. Data collection by observation, interview, documentation and test variation skill of student showed that the increasing of the first cycle was 67,12% and the second cycle was 73,87%.